Improving Problem-Solving Ability in IPAS Through Problem-Based Learning Integrated with the TaRL Approach in Grade V Elementary School - Atika Dewi (SEAQIS Journal of Science Education, 2026)
Problem-solving ability is an essential skill that needs to be developed from an early stage to train students to analyse situations and determine appropriate solutions. However, several studies indicate that students’ problem-solving ability is still relatively low. This study aimed to examine the effectiveness of a problem-based learning (PBL) model integrated with the Teaching at the Right Level (TaRL) approach in improving problem-solving ability in IPAS learning among fifth-grade elementary school students. This study employed a pre-experimental method with a one-group pretest–post-test design involving 15 fifth-grade students from an elementary school at Pati regency. The research instruments consisted of written tests used for the pretest and post-test and observation sheets to assess students’ problem-solving processes. Data analysis was conducted through triangulation by comparing the results of written test analysis with classroom observation results. The written test data were analysed using descriptive statistics and N-Gain analysis. The results showed that the implementation of the PBL model integrated with the TaRL approach contributes to the improvement of students’ problem-solving ability in IPAS learning. The written test analysis indicated an increase in the average score from the pretest to the post-test of 13.34%, along with an increase in the number of students who achieved criteria for learning objectives. The N-Gain analysis result of 0.56 indicated a moderate improvement in students’ problem-solving ability. In addition, the comparison between the written test results and classroom observations showed a consistent pattern in students’ problem-solving performance.